2000
DOI: 10.1103/physrevlett.85.5360
|View full text |Cite
|
Sign up to set email alerts
|

Energy Landscape of a Lennard-Jones Liquid: Statistics of Stationary Points

Abstract: Molecular dynamics simulations are used to generate an ensemble of saddles of the potential energy of a Lennard-Jones liquid. Classifying all extrema by their potential energy u and number of unstable directions k, a well-defined relation k(u) is revealed. The degree of instability of typical stationary points vanishes at a threshold potential energy u(th), which lies above the energy of the lowest glassy minima of the system. The energies of the inherent states, as obtained by the Stillinger-Weber method, app… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
289
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 189 publications
(308 citation statements)
references
References 22 publications
15
289
2
Order By: Relevance
“…Empirically, a direct validation of Goldstein scenario in liquids is difficult. Several numerical analysis [137][138][139] have claimed to observe a transition in the energy landscape at T MCT , but in our opinion the interpretation of these results is disputable 1 . Another intriguing .…”
Section: Glass Transition and Soft Modes In Hard Sphere Liquidsmentioning
confidence: 56%
“…Empirically, a direct validation of Goldstein scenario in liquids is difficult. Several numerical analysis [137][138][139] have claimed to observe a transition in the energy landscape at T MCT , but in our opinion the interpretation of these results is disputable 1 . Another intriguing .…”
Section: Glass Transition and Soft Modes In Hard Sphere Liquidsmentioning
confidence: 56%
“…Despite claims based on numerical results that T c marks a real change in the topology of the landscape [33,34,35], there are strong indications that this is at best only a crossover [36,37], and at worst a biased interpretation of numerical data [38]. For instance, careful numerical studies have shown that the saddle index n s (T ) remains positive even below T c [36].…”
Section: B and Its Problems And Contradictionsmentioning
confidence: 99%
“…The quantities n s and e s were estimated numerically in simulations of supercooled liquids [33,34]. It was found that both functions decrease when T decreases, and extrapolations were performed that indicated n s (T c ) = 0.…”
Section: B Absence Of "Geometric Transition"mentioning
confidence: 99%
See 2 more Smart Citations